Hallazgo de una bula incunable desconocida en la catedral de Valencia. Contribución a la imprenta de Antonio Téllez (Toledo, 1495). - BOSCÁ CODINA, JOSÉ VICENTE; MANDINGORRA LLAVATA, MARÍA LUZ (Scripta, 2015)
The aim of this paper is to analyse a copy of a Papal bull granting indulgence for the living. It was issued in favour of the Crusaders, and printed in Toledo in 1495. It is written in Catalan, and has been found in the Valencia Cathedral Archive. We wish to bring its existence to the attention of scholars, as it is the only surviving copy that we know of.